Sgr A West in the light of molecules: cold and dense gas east of the circumnuclear disk. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Moser, Lydia; Eckart, A.; Borkar, A.; García-Marin, M.; Kunneriath, D.; Jalali, B.; Sabha, N.; Shahzamanian, B.; Valencia-S., M.; Zamaninasab, M.; Bronfman, L.; Finger, R.
Abstract: We present the very first detection of N2 H + J = (1 – 0) and CH3 OH(2k −1k ) line emission on 5″ scales in the circumnuclear disk (CND) around Sgr A*. The emission matches the position and shape of the dark clouds in the near-infrared. Our findings suggest that these molecular clouds in the eastern CND are significantly colder and denser than the rest of the CND, and partially shocked. The research on these dark clouds will contribute to understanding the processes of star formation close to a supermassive black hole.